DAS181 treatment of severe parainfluenza type 3 pneumonia in a lung transplant recipient. Issue 1 (26th December 2012) - Drozd, D.R.; Limaye, A.P.; Moss, R.B.; Sanders, R.L.; Hansen, C.; Edelman, J.D.; Raghu, G.; Boeckh, M.; Rakita, R.M.
Abstract Parainfluenza virus (PIV) may cause life‐threatening pneumonia in lung transplant patients and there are no proven effective therapies. We report the use of inhaled DAS181, a novel sialidase fusion protein, to treat severe PIV type 3 pneumonia in a lung transplant patient. Treatment was well tolerated and associated with improvement in oxygenation and symptoms, along with rapid clearance of PIV. DAS181 should be systematically evaluated for treatment of PIV infection in transplant recipients.